Magnetic techniques for the detection and determination of xenobiotics and cells in water - Safarik, Ivo; Horska, Katerina; Pospiskova, Kristyna; Safarikova, Mirka (Analytical and bioanalytical chemistry, 2012)
Magnetic techniques based on the application of magnetic nanoparticles and microparticles and films have been successfully used for the determination and detection of different types of xenobiotics (e.g. herbicides, insecticides, fungicides, aromatic and polyaromatic hydrocarbons, pentachlorophenol and heavy metal ions) as well as viruses, microbial pathogens and protozoan parasites in water samples. Preconcentration of xenobiotics from large volumes of samples can be performed using magnetic solid-phase extraction, stir-bar sorptive extraction and related procedures. This review provides basic information about these techniques. Published examples of successful applications document the importance of these simple and efficient procedures employing magnetic materials.
Keywords: látky znečišťující vodu; Adsorption; voda; Water Pollutants; mikrobiologie vody; magnetismus; xenobiotika; Water; Water Microbiology; adsorpce; Magnetics; Xenobiotics